2021
DOI: 10.1101/2021.05.20.445008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute SARS-CoV-2 infection is associated with an expansion of bacteria pathogens in the nose including Pseudomonas Aeruginosa

Abstract: Much of the research conducted on SARS-CoV-2 and COVID-19 has focused on the systemic host response, especially that generated by severely ill patients. Very few studies have investigated the impact of acute SARS-CoV-2 within the nasopharynx, the site of initial infection and viral replication. In this study we profiled changes in the nasal microbial communities as well as in host transcriptional profile during acute SARS-CoV-2 infection using 16S amplicon sequencing and RNA sequencing. These analyses were cou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 84 publications
(87 reference statements)
1
6
0
Order By: Relevance
“…Overall, our results showing a down-regulation of key myeloid markers on COVID-PBMCs, associated with an 'unfavorable' Th2 biasing of lymphoid cytokines suggested that this phenotype may be conducive to a greater sensitivity/lesser responsiveness to bacterial microbes such as Pseudomonas aeruginosa (P.a), an important nosocomial pathogen in ICU settings, and in COVID patients, as demonstrated previously (33)(34)(35)(36), and in the present study (Supplementary Tables S4-S6).…”
Section: Unstimulated Pbmcs Lymphoid Cytokines Outputsupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, our results showing a down-regulation of key myeloid markers on COVID-PBMCs, associated with an 'unfavorable' Th2 biasing of lymphoid cytokines suggested that this phenotype may be conducive to a greater sensitivity/lesser responsiveness to bacterial microbes such as Pseudomonas aeruginosa (P.a), an important nosocomial pathogen in ICU settings, and in COVID patients, as demonstrated previously (33)(34)(35)(36), and in the present study (Supplementary Tables S4-S6).…”
Section: Unstimulated Pbmcs Lymphoid Cytokines Outputsupporting
confidence: 81%
“…We show that COVID patients have an increased proportion of lowdensity neutrophils (LDNs), which produce high levels of proteases (particularly, NE, MMP-8 and MMP-9) (unlike non-COV-ICU patients), which are partly responsible for causing type II alveolar cell damage in co-culture experiments. In addition, we showed that M-and ICU-COVID PBMCs had reduced responsiveness towards further live Pseudomonas aeruginosa (PAO1) infection, an important pathogen colonizing COVID patients in ICU (33)(34)(35)(36), as assessed by an impaired secretion of myeloid cytokines (IL-1, TNF, IL-8,…). By contrast, lymphoid cytokines (in particular type 2/type 3) levels remained high, both basally and post PAO1 infection, as reflected by the unimpaired capacity of T cells to proliferate, when stimulated with anti-CD3/CD28 beads.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies examining correlations between the URT microbiota and SARS-CoV2 infection since the beginning of the COVID-19 global pandemic. These studies indicate that the microbiota is shifted with an enrichment of pathobionts and opportunistic pathogens in COVID-19 patients compared to non-infected individuals (Engen et al, 2021;Merenstein et al, 2021;Rhoades et al, 2021). We note that at the time of writing, some of these studies have not yet been peer reviewed.…”
Section: Adenovirus/coronavirusmentioning
confidence: 99%
“…Secondary bacterial infection is an inevitable result of pulmonary dysbiosis and respiratory tract distortion caused by SARS-CoV-2 infection, making it a fatal disease (Hanada et al, 2018;Jose and Desai, 2020). Illustratively, SARS-CoV-2 infection creates a respiratory environment that permits the invasion of the abundance of bacterial pathogens through a distinct shift in the composition of the microbiome (Rhoades et al, 2021), with genetic traits suitable for chronic infections (Qu et al, 2022). This phase causes exacerbation of illness, and the clinical diagnosis and treatment are more complicated (Bosch et al, 2013), causing morbidity and mortality of critical patients to insanely raise (Sharifipour et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa was notified as the most abundant superinfecting bacterial in the sputum samples and bronchoalveolar lavage fluids (BALF) (Qu et al, 2021;Rhoades et al, 2021). In this context, Rothia comes next in existence in the nasal microbiome, and it is considered the best predictor of SARS-CoV-2 vRNA infection in patient samples.…”
Section: Introductionmentioning
confidence: 99%